2009
DOI: 10.1183/09031936.00084808
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide hydroxamic acid: a potential epigenetic therapeutic agent for lung fibrosis?

Abstract: Pulmonary fibrosis represents a fatal stage of interstitial lung diseases of known and idiopathic aetiology. No effective therapy is currently available. Based on an indication-discovery approach we present novel in vitro evidence that the histone deacetylases inhibitor suberoylanilide hydroxamic acid (SAHA), an FDA approved anti-cancer drug, has antifibrotic and anti-inflammatory potential.Human lung fibroblasts (fetal, adult and idiopathic adult pulmonary fibrosis) were treated with transforming growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 31 publications
10
68
0
Order By: Relevance
“…In addition, MS-275 and SAHA suppressed lipo poly saccharide (LPS)-induced NFκB p65 nuclear accumulation, IL-6, IL-18 and nitric oxide (NO) secretion as well as downregulated proangiogenic VEGF and MMP-2 and MMP-9 production in E11 cells at submicromolar levels (47). TSA or SAHA decreased fibroblast proliferation and extracellular matrix production in murine models of fibrosis (53), and blocked transforming growth factor β-(TGFβ) induced differentiation of fibroblasts into myofibroblasts and impaired epithelial-mesenchymal transformation both in vitro and in vivo. HDACi also can inhibit production of matrix metalloproteinases (MMPs) that contribute to tissue destruction (for example, via collagen and aggrecan breakdown) in inflammatory disease (54).…”
Section: Influence On T-cell Differentiationmentioning
confidence: 99%
“…In addition, MS-275 and SAHA suppressed lipo poly saccharide (LPS)-induced NFκB p65 nuclear accumulation, IL-6, IL-18 and nitric oxide (NO) secretion as well as downregulated proangiogenic VEGF and MMP-2 and MMP-9 production in E11 cells at submicromolar levels (47). TSA or SAHA decreased fibroblast proliferation and extracellular matrix production in murine models of fibrosis (53), and blocked transforming growth factor β-(TGFβ) induced differentiation of fibroblasts into myofibroblasts and impaired epithelial-mesenchymal transformation both in vitro and in vivo. HDACi also can inhibit production of matrix metalloproteinases (MMPs) that contribute to tissue destruction (for example, via collagen and aggrecan breakdown) in inflammatory disease (54).…”
Section: Influence On T-cell Differentiationmentioning
confidence: 99%
“…However, a TSA structural analogue, suberoylanilide hydroxamic acid (SAHA) (Vorinostat; Merck, Whitestation, NJ, USA), is currently being investigated in a number of clinical trials, and is the first US Food and Drug Administration approved HDACi to treat cutaneous T-cell lymphoma [8]. Previously, studies have indicated that TSA and SAHA have anti-inflammatory [9] and anti-fibrotic properties [10][11][12] in fibroblasts, such as inhibition of cell proliferation, collagen production and myofibroblastic differentiation. However, few studies have explored the mechanisms and effects of SAHA on apoptosis and their mechanisms in IPF fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…By inhibition of HDACs activity these compounds induce cellcycle arrest and apoptosis (9,10). In addition, there were increasing evidence suggesting that HDAC inhibitors, influenced proinflammatory cytokine synthesis (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…Although histone acetylation is generally associated with transcriptional activation, HDI can either increase or decrease expression of specific genes. HDI are of prime interest in cancer research because they induce apoptosis and cell cycle arrest in malignant cells and are anti-angiogenic (9,10). Suberoylanilide Hydroxamic Acid (SAHA) is the HDI targeted to the class I and class II HDAC enzymes (7).…”
Section: Introductionmentioning
confidence: 99%